Edukasi Peningkatan Motivasi Kunjungan Kesehatan Gigi Dan Mulut di Puskesmas Muara Siberut, Kabupaten Kepulauan Mentawai, Provinsi Sumatera Barat: Education to Increase Motivation of Oral Health Utilization at Puskesmas Muara Siberut, Mentawai Islands Regency, West Sumatra Province - Rahmi, Eni; Sari, Desy Purnama; Rafi, Soni Muhammad; Tita, Azizah Rahma; Khairah, Imalatunil; Syahti, Fitria Dwi; Ikhwani, Awal (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Mentawai ethnic group has unique traditions like anterior teeth mutilation and the use of herbal medicines by sikerei or siaggai laggek (traditional doctor) that cause low visitation to community health centers. The low level of puskesmas utilization rate impacts the failure to achieve the work program of the puskesmas in improving public health status, especially oral health, then influences the quality of health center services (puskesmas). This activity aims to increase community visits and the utilization of health services in Puskesmas Muara Siberut. This activity lasted on July 21, 2023, and was carried out in Muntei Village (work area of the Puskesmas Muara Siberut), South Siberut District, Mentawai Islands Regency, West Sumatra Province. This service uses four methods: observation, planning, action, and evaluation. The results obtained from this activity were an increase in public knowledge regarding ideal behavior in increasing motivation to utilize dental and oral health services at the Muara Siberut Community Health Center through post-test scores at the end of the counseling session. With this service activity, it is hoped that the attitudes and actions of the oral health utilization will increase significantly, along with the high level of public knowledge after being given counseling, so that it will also have an impact in improving the degree of oral health communities